IMPROVING THE STUDENTS' LISTENING COMPREHENSION THROUGH LEARN ENGLISH LISTENING APP: A CLASSROOM ACTION RESEARCH - Setiawati, Sari; Yuliana, Yohanes Gatot Sutapa; Regina, Regina (EXPOSURE : JURNAL PENDIDIKAN BAHASA INGGRIS, 2024)
This research investigated the impact of the "Learn English Listening App" on eighth-grade students' listening comprehension. The design of Classroom Action Research (CAR) was used in this study. Two cycles of pre and post-tests, observations, and interviews were conducted. In the first cycle, the app did not lead to a statistical improvement in listening. The mean post-test score (57) was lower than the mean pre-test (61). The observations indicated a positive attitude towards the app, yet some students underutilized its potential, highlighting the need for further support. Interviews provided insights, emphasizing the importance of additional guidance in applying the application. In the second cycle, the students were maximized to utilize the app, significantly improving listening comprehension (mean score: 72.67). The t-test analysis showed a difference (t ≈ 2.43) between the pre and post-test, confirming the app's effectiveness. The observations during the second cycle showed enhanced engagement. The "Learn English Listening App" proved valuable for enhancing eighth-grade students' listening skills. The classroom action research approach allowed for iterative adjustments, contributing to improved scores. In conclusion, the second cycle's t-test results, supported by classroom observations and interviews, provide robust evidence of the app's positive impact. Educators at Islam Al-Azhar 17 Pontianak and similar settings can consider integrating technology-based interventions like the app to enhance students' listening comprehension. Further research could explore its long-term effects and impact on other language skills.